Distinguishing between isthmic thyroglossal duct cyst and goitre on nuclear thyroid scan: A case report - Yetunde Ajoke Onimode (Academy of Family Physicians of Malaysia, 2021)
Thyroglossal duct cysts, which are the most frequently encountered congenital cervical anomalies in children, occur due to embryologic remnants of the thyroglossal duct. Although diagnosis may be challenging, clinicians can be aided by imaging and fine-needle aspiration biopsies. We describe the clinical management of a two-year-old boy with a thyroglossal duct cyst mimicking a goitre on a pertechnetate thyroid scan.